IMPLEMENTASI MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA TUNADAKSA KELAS VII DI SLB NEGERI I MAKASSAR - Sitti Hartinah Hartinah Nurul Kubra; Agus Marsidi; Mufa’adi Mufa’adi (-, 2026)
ABSTRACTSITTI HARTINAH NURUL KUBRA, 2022.The Use of the Poblem Based Learning Method to Improve Science Learning Outcomes of Class VII Handicapped Students at SLB Negeri 1 MAKASSAR. Thesis. Guided by Drs. Agus Marsidi, M.Si, and Drs. Mufa'adi, M.Si. Special Education Study Program, Faculty of Education, Makassar State University. This study examines the low science learning ability of students with disabilities in science subjects, classifying living things and objects based on the characteristics observed in SLB Negeri 1 Makassar. The formulation of the problem in this study is: (1) What is the description of science learning outcomes in grade VII students of the Disabled at SLB Negeri 1 Makassar before the use of the Problem Based Learning method (2) What are the learning outcomes of science in grade VII students of the Disabled at SLB Negeri 1 Makassar after the use of the Problem Based Learning method?. The approach of this research is quantitative research with a descriptive type of research. The research subject is one student of the handicapped class VII. The data collection technique was carried out using the provision of tests. Data analysis uses the results of the test before and after the treatment, describes the results of the test before and after the treatment, and compares the learning results before and after the treatment. The results of the study show that: (1) the ability to learn science in students with disabilities is very poor, (2) the ability to learn science in students with disabilities increases after the use of the Problem Based Learning method.